Schizophrenia and Suicide Attempts: Findings from a Representative Community-Based Canadian Sample. (10th February 2016) - Fuller-Thomson, Esme; Hollister, Bailey
Abstract : This study examined factors associated with suicide attempts among those with schizophrenia (n = 101 ) versus those without (n = 21, 643 ) in a representative sample of noninstitutionalized Canadians. The lifetime prevalence of suicide attempts among persons with schizophrenia was 39.2% versus 2.8% of nonafflicted individuals. After adjusting for sociodemographics, childhood adversities, substance abuse/dependence, depression/anxiety, and chronic pain, those with schizophrenia had 6 times the odds (OR = 6.47) of attempting suicide. Among persons with schizophrenia, suicide attempts were associated with female gender (OR = 4.59), substance abuse/dependence (OR = 6.31), depression (OR = 4.93), and childhood physical abuse (OR = 5.75). Community-dwelling persons with schizophrenia appear to be at high risk for suicide attempts.